Precise orbit determination based on COST-G time-variable gravity fields - Meyer, Ulrich; Peter, Heike; Förste, Christoph; Lasser, Martin; Jäggi, Adrian (2022)
The Combination Service for Time-variable Gravity fields (COST-G) provides monthly gravity fields, combined from the individual solutions of the COST-G analysis centers and additional partner analysis centers derived from GRACE/GRACE-FO inter-satellite GPS and K-band ranging data. The Precise Orbit Determination (POD) of Earth observation satellites in Low Earth Orbits (LEO) relies on accurate and up-to-date information on the Earthâ?Ts gravity field and its time-variations. We study POD results of the Sentinel-2B, -3B and -6A satellites based either on the monthly COST-G combinations, available with a latency of 2-3 months, or on Fitted Signal Models (FSM) derived on the basis of the COST-G time-series of monthly gravity fields, which allow for the prediction of secular and seasonal gravity variations over several months and therefore may be used in operational LEO POD. Special focus is put on the fit interval of the FSM and the impact of episodic events, e.g. the massive ice melt in Greenland in the summer of 2019, on the performance of the gravity-predictions for POD.